2023
DOI: 10.1007/s00784-023-05138-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of stannous fluoride-containing mouth rinse and toothpaste prevents enamel erosion in vitro

Apichaya Jiemkim,
Thipawan Tharapiwattananon,
Siriporn Songsiripradubboon

Abstract: Objective To compare the protective effect of commercial stannous-containing mouth rinses on enamel erosion in a simulated 5-day in vitro cycling model. Materials and methods 81 human enamel specimens were embedded in resin blocks and divided into nine groups as follows; group 1: stannous fluoride (1000SnF2) toothpaste; groups 2,3, and 4 were the same as group 1 plus Elmex®, PerioMed™, and Meridol®, respectively, group 5: stannous fluoride (1450SnF2) tooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Some in vitro studies have also demonstrated positive results for using products containing polyvalent metal ions (tin or titanium) or products with added amino acids, peptides, or proteins in preventing dental erosion [ 42 ]. Fluoridated products containing metal cations, such as stannous was found to be a better option than other fluoride solutions in controlling dental erosion [ 43 ].…”
Section: Tooth Wear Management In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some in vitro studies have also demonstrated positive results for using products containing polyvalent metal ions (tin or titanium) or products with added amino acids, peptides, or proteins in preventing dental erosion [ 42 ]. Fluoridated products containing metal cations, such as stannous was found to be a better option than other fluoride solutions in controlling dental erosion [ 43 ].…”
Section: Tooth Wear Management In Older Adultsmentioning
confidence: 99%
“…The tin-rich deposition was more resistant to an acid attack, and hence, it prevented the underlying tooth substance from dental erosion [ 42 ]. An in vitro study found that the combined use of stannous fluoride-containing mouth rinses and toothpastes can increase their protective effect against dental erosion [ 43 ]. Toothpastes with added polymers such as sodium hexametaphosphate and chitosan, which adsorb to dental surfaces and create an additional protective layer, may protect against dental erosion [ 8 ].…”
Section: Tooth Wear Management In Older Adultsmentioning
confidence: 99%